Meta-Analisis Pengaruh Penggunaan Media Roda Putar Terhadap Hasil Belajar Matematika di Sekolah Dasar - Mar'atus Solichah; Akhwani Akhwani; Sri Hartatik; Syamsul Ghufron (Wahana Sekolah Dasar, 2020)
This study aims to analyze the effect of the use of the wheel media on student mathematics learning outcomes in elementary schools. This research uses meta-analysis method. Research data on the use of the wheel media is analyzed deeply to find the effect of the wheel media on the results of learning mathematics. This research begins by formulating research topics, exploring relevant research results for analysis. Data were analyzed using quantitative descriptive analysis. The results showed the use of the wheel media in learning mathematics in elementary schools could improve mathematics learning outcomes of elementary school students. Based on the results of the analysis of the use of the wheel media in mathematics learning in elementary schools can improve mathematics learning outcomes of elementary school students starting from the lowest 5.57% to the highest 545.67% with an average of 121.83%.